DOES TECHNICAL PROGRESS MITIGATE CLIMATE EFFECT ON CROPS YIELD IN PAKISTAN? - S. Ali; Y. Liu; 2; A. Nazir; M. Ishaq; S. B. Khan; Abdullah; T. Shah (Journal of Animal and Plant Sciences, 2020)
Efforts to sustain the global food system are suffering from the serious challenge of agricultural vulnerability to climate change. The current study is aimed at exploring the relation among yields of major food crops (wheat, rice and maize), climate change (temperature and rainfall), and technical progress (fertilizer and agricultural machinery) in Pakistan. In this regard, Autoregressive Distributed Lag (ARDL) model is employed using time series data over a period to time 1989 to 2015. To determine the co-integration, bound F-test results validate equilibrium for a long-run and short-run between yields of major food crops, temperature, rainfall, fertilizer and agricultural machinery. The long-run estimates indicate that area and temperature have a significant yet found a negative impact on wheat yield. However, for wheat yield, the coefficient of fertilizer usage was positive and had a significant effect. For rice crop, the coefficient of rainfall was found negative and had a statistically significant effect. The study concludes that climatic factors have a moderately negative impact on the yields of major food crops. The technical instruments and machinery needed to be enhanced since it plays an important role in increasing the yields of the crops. To deal and mitigate the negative effects of climate change, the government needs to develop agricultural adaptation policies, improve irrigation facilities and introduce high yielding and disease-resistant varieties for these food crops to ensure food security in the country.
Keywords: Climate change; technical progress; crops yield; ARDL model; Pakistan